2021
DOI: 10.3389/fonc.2021.691372
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Signature of Hepatocellular Carcinoma and Analysis of Immune Infiltration Based on m6A-Related lncRNAs

Abstract: The relationship between m6A-related lncRNAs and prognosis in hepatocellular carcinoma (HCC) is not yet clear. We used Lasso regression to establish a prognostic signature based on m6A-related lncRNAs using a training set from TCGA, and then verified the signature efficacy in a test set. Fluorescence quantitative real-time PCR (qPCR), Survival analysis, clinical risk difference analysis, immune-related analysis, and drug-sensitivity analysis were conducted. The results revealed that 1,651 lncRNAs were differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In addition, the predictive accuracy of the risk score was assessed by the time-dependent ROC analysis at 1, 2, and 3 years, with area under the curve (AUC) values of 0.787, 0.761, and 0.739, respectively ( Figure 2H ), Furthermore, the AUC value of OS for the risk score was significantly higher than those for age, sex, tumor stage, tumor pathological grade, and tumor staging ( Figure 2I , Supplementary Figure S3 ). DCA curve and IDI were used to compare the discriminative ability between our model and the previously reported lncRNA prediction model for HCC ( Li et al, 2020 ; Guo et al, 2021a ; Guo et al, 2021b ; Huang et al, 2021b ; Wang et al, 2021b ; Lei et al, 2021 ; Li et al, 2021 ). DCA indicated that our pyroptosis-related lncRNA signature had positive net benefits and superiority compared with the previously reported lncRNA prediction signature for HCC ( Supplementary Figure S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the predictive accuracy of the risk score was assessed by the time-dependent ROC analysis at 1, 2, and 3 years, with area under the curve (AUC) values of 0.787, 0.761, and 0.739, respectively ( Figure 2H ), Furthermore, the AUC value of OS for the risk score was significantly higher than those for age, sex, tumor stage, tumor pathological grade, and tumor staging ( Figure 2I , Supplementary Figure S3 ). DCA curve and IDI were used to compare the discriminative ability between our model and the previously reported lncRNA prediction model for HCC ( Li et al, 2020 ; Guo et al, 2021a ; Guo et al, 2021b ; Huang et al, 2021b ; Wang et al, 2021b ; Lei et al, 2021 ; Li et al, 2021 ). DCA indicated that our pyroptosis-related lncRNA signature had positive net benefits and superiority compared with the previously reported lncRNA prediction signature for HCC ( Supplementary Figure S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, due to lack of dataset of AEG immunotherapy, we could not further explore the correlation between the pyroptosis-related lncRNA risk model and PD-L1/PD-1 blockade therapy. Several studies found that lncRNA risk models have potential value in predicting drug sensitivity [46][47][48]. A recently study [14] also identi ed a six immune-related lncRNA signature has a good predictive effect on the sensitivity of chemotherapy drugs in AEG, such as cisplatin, doxorubicin, gemcitabine, paclitaxel, et al In current study, we used the oncoPredict R package to comprehensively estimate the predictive value of drug sensitivity of the three pyroptosis-related lncRNA risk model.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, YTHDF1 expression is higher in Stage III/IV HCC than in Stage I/II HCC 145 . In addition, m6A‐modified lncRNAs may predict the OS of HCC patients and act as an independent prognostic factor for HCC 146 …”
Section: Potential Clinical Applications Of M6a In Hepatitis B Virus‐...mentioning
confidence: 96%
“…145 In addition, m6A-modified lncRNAs may predict the OS of HCC patients and act as an independent prognostic factor for HCC. 146 However, some issues should be addressed to achieve broad clinical applications of m6A in the diagnosis, treatment, and prognosis of HBV-associated HCC. qPCR amplification and methylated RNA immunoprecipitation sequencing (MeRIP-Seq) are main detection methods for m6A, while both of them have deficiencies.…”
Section: Potential Clinical Applications Of M6a In Hepatitis B Virus-...mentioning
confidence: 99%